LOCATION AND MOTIVATION INFLUENCE ON THE DECISION TO VISIT THE TEMBELING, NUSA PENIDA - Putriningsih, Desak Putu Erlita; Suwintari, I Gusti Ayu Eka; Widada, Magdalena Cahyani Priyastika Ningsih (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2023)
This research is the first to investigate the influence of location and motivation on domestic tourists’ decisions to visit the Tembeling Springs tourist attraction in Nusa Penida, Bali, which is the result of applied science in the field of economics. The research aims to explore how location and motivation, two critical factors in tourism behavior, can affect the attractiveness and satisfaction of domestic tourists in Tembeling Springs, a natural and cultural destination in Nusa Penida, Bali. Quantitative methodology was used by conducting a survey of 200 domestic tourist respondents. The research results show that location influences tourists’ visiting decisions, with preferences for accessibility and adequate facilities. Motivation also plays an important role. The desire to relax and enjoy the beauty of nature is an essential factor. The research reveals that location and motivation positively and significantly affect tourist satisfaction, influencing the intention to revisit and recommend Tembeling Springs to others. These findings can be used to optimize the marketing and development of tourist attractions and increase tourist satisfaction. The novelty of this research is that it introduces a new model of tourist behavior in Tembeling Springs, which is different from the conventional models of tourist behavior in Bali, which focuses on the natural and cultural attractions, such as the beaches, temples, and festivals. The research contributes to the literature on tourism and economics by highlighting the role of location and motivation in attracting and satisfying domestic tourists in Tembeling Springs.